Meaningful practices of citizenship in urban middle-class Peru : the case of political blogging - Winter, Franka C. (Irish School of Ecumenics, 2013)
This thesis discusses political blogging as a meaningful praxis of citizenship among members of the (traditional) urban middle classes in post-transitional Peru. It examines the meanings political bloggers attach to citizenship and the ways in which these meanings translate into practice, taking into account the historical, social, and political context of post-transitional Peru. The thesis asks: - What do political bloggers (as members of the urban middle classes) understand by "citizenship" and where do they draw the limits of citizenship? - How do these meanings relate to and are shaped by the post-transitional context? - How do they see blogging as citizenship in "real life"? - What are the exclusionary practices resulting from the "limits of citizenship"? The thesis argues that Peruvian bloggers' notions of citizenship emphasised vigilance and deliberation, rather than rights and inclusion. In the historical context of post-transitional Peru, memories of mass media corruption and perceptions of structural and cultural continuity played an important role in shaping the meanings and practices of citizenship. Vigilant and deliberative citizenship assumed a link with marginality, which formed a crucial precondition for being a "good" and credible citizen. It was furthermore linked to a specific mindset and understood in terms of "remembering the past/interpreting the present differently", keeping checks on "the powerful", and "correcting" collective memories that idealised the Fujimori government. In relationship to the wider public sphere, many bloggers perceived the blogosphere as such a "marginal" space, where deliberative and vigilant citizenship could be practiced. However, others felt that the "real-existing" blogosphere was not a suitable space for either deliberation or vigilance: because actual bloggers "lacked marginality" and used power against other bloggers (restricting their vigilant and deliberative activities); because the blogosphere was too homogenous for meaningful deliberation; or, as others argued, too polarised and aggressive. Examining practices of "exclusion through citizenship", the thesis finally argues that the construction of deliberative citizenship went along with the construction of its "constitutive outside" (Butler 1993): that which doesn't count as civic. I call these boundaries the "limits of deliberation". Overstepping these limits could result in being branded a "troll" (essentially a non-citizen, who can be excluded and subjected to abuse, becoming the object, rather than subject of vigilant citizenship) and being excluded from deliberation. While bloggers were eager to stress that the limits of deliberation referred to offensive speech only and should not affect political dissent, I shall show that in praxis drawing the line between the political and the offensive was not always easy. This was particularly true in struggles over collective memories and the interpretation of the recent past and its legacy in contemporary Peru. The thesis draws on qualitative and quantitative data, including semi-structured interviews, observational data, debates from the Peruvian blogosphere, and biographic surveys. These were analysed using tools of Grounded Theory and Discourse Analysis. From a disciplinary focus of political sociology, the thesis contributes to the wider field of citizenship studies by studying the meanings, practices, and restrictions of citizenship "on the ground". More specifically, it contributes both to citizenship studies and to wider sociological issues in Peru by focussing on notions and practices of citizenship among the (traditional) urban middle classes, a sector of Peruvian society which to date has received very limited scholarly attention.
Keywords: Ecumenics, Ph.D.; Ph.D. Trinity College Dublin